2021
DOI: 10.1111/faf.12560
|View full text |Cite
|
Sign up to set email alerts
|

Global status of groundfish stocks

Abstract: We review the status of groundfish stocks using published scientific assessments for 349 individual stocks constituting 90% of global groundfish catch. Overall, average stock abundance is increasing and is currently above the level that would produce maximum sustainable yield (MSY). Fishing pressure for cod‐like fishes (Gadiformes) and flatfishes (Pleuronectiformes) was, for several decades, on average well above levels associated with MSY, but is now at or below the level expected to produce MSY. In contrast,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Although the challenges faced by fisheries and their impacts on ecosystems are widespread, the tendency toward oversimplification and a "doom and gloom" narrative has eclipsed other assessments (Worm et al, 2009;Branch et al, 2011) that showed large geographic and taxonomic variation in the state of fish stocks and highlighted some positive trends in at least some areas. Recent research (Zimmermann and Werner, 2019;Hilborn et al, 2020;Hilborn et al, 2021) has found encouraging trends toward improved sustainability of fisheries over the past two decades in some stocks and regions, notably the Northeast Atlantic Ocean. These positive trends do not imply that all issues are solved, but indicate that improvement is possible.…”
Section: Examples For Optimism On Fisheries Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Although the challenges faced by fisheries and their impacts on ecosystems are widespread, the tendency toward oversimplification and a "doom and gloom" narrative has eclipsed other assessments (Worm et al, 2009;Branch et al, 2011) that showed large geographic and taxonomic variation in the state of fish stocks and highlighted some positive trends in at least some areas. Recent research (Zimmermann and Werner, 2019;Hilborn et al, 2020;Hilborn et al, 2021) has found encouraging trends toward improved sustainability of fisheries over the past two decades in some stocks and regions, notably the Northeast Atlantic Ocean. These positive trends do not imply that all issues are solved, but indicate that improvement is possible.…”
Section: Examples For Optimism On Fisheries Recoverymentioning
confidence: 99%
“…However, in the early 2000s, persistent overfishing prompted policy changes (EU, 2002) to improve the management of fish stocks and facilitate their rebuilding. After initial stagnation (Froese and Proelß, 2010), signs of a trend reversal started to emerge (Cardinale et al, 2013;Fernandes and Cook, 2013), with clear improvements in their sustainability in recent years (Zimmermann and Werner, 2019;Hilborn et al, 2021).…”
Section: Examples For Optimism On Fisheries Recoverymentioning
confidence: 99%
“…The concept of MSY was developed to make single species stock assessments and estimation of stock status (Hilborn et al, 2021). Several studies (Larkin, 1977;Mace, 2001) have shown the difficulties of estimating MSY in a multi-species context, and set harvest strategies based on MSY that account for fish stock and predator-prey interactions, and climate driven processes.…”
Section: The Case For Legal Reformmentioning
confidence: 99%
“…A majority of commercially fished stocks are considered overfished (FAO, 2020 ), and effective catch per unit of effort is decreasing despite that the size of the fishing fleet has doubled since the 1950s (Rousseau et al, 2019 ). The future could still be optimistic as the status of global fish stocks is not homogenous but rather considerably varying among fisheries and locations, demonstrating the influence of successful management strategies (Hilborn et al, 2021 ). The general trend implies that while poorly managed stocks continue to decline, the biomass of well‐managed stocks is in stabilising or rebuilding state (Worm & Branch, 2012 ).…”
Section: Introductionmentioning
confidence: 99%